Conditions, methods and principles of healthcare system records integration – part 1 - Nyczaj, Krzysztof (Polish Journal of Public Health, 2009)
The article is the explication of refl ections on the role and importance of records in the healthcare information system the author has taken up in the weekly “Służba Zdrowia” and monthly journals: “National Medical Outline” and “Health Manager”. The article covers the valid definitions of: public record, official record, administrative record, and next there is discussed an issue of inadequacy of public record definition that has been introduced by the act of information technology implementation in the healthcare system. This definition excludes from the public records many healthcare records which constitute important information technologyrelated infrastructural elements of the state on the one hand, and on the other hand, it affords a public status to the typical private records. The article points out to the considerable difference between the register, files and the specification. Their distinction is one of the key issues in the context of introducing information order in healthcare. The models of information system functioning in Polish and Scandinavian healthcare systems were discussed. The review of records classification used in the subject literature was made, as well as, an attempt of designing such a classification for healthcare records was made. The developed classification was used for designing of models for individual types of records: service providers, medical workers and the customers. In the models, among other things, the desired hierarchical and informational relationships between individual types of data sets in health protection were indicated, particularly between different types of administration records.